Contribution to the Enumeration and Study of the Podocarpus L’Hér. ex Pers. s.str. (Podocarpaceae) Taxa in Vietnam - Duyen, Nguyen Thi Thanh; Thanh, Nguyen Trung; Loc, Phan Ke (VNU Journal of Science: Natural Sciences and Technology, 2017)
Podocarpus is a small genus of conifers, having some scientific and economic values. Vietnam is recognised as one of 10 conifer “hotspots” in the world with 90% of total taxa threatened. Goal of this study is to enumerate taxa of the Podocarpus s. str . Methods of classical external morphology study are applied. 46 historical collecting numbers and 7 new collecting numbers were studied, revisedand hosted in HNU. Their scientific names were comparied with Protologue. Two native species Podocarpus pilgeri Foxw. and Podocarpus neriifolius D.Don with two varieties, var. neriifolius and var. annamiensis (N.E. Gray) L.K.Phan ms. and Podocarpus macrophyllus (Thunb.) Sweet as ornamental are listed. Annotations for each taxon mostly include the following informations: currently accepted scientific name, literature references to bona fide uses of these names, main synonyms used in regional literature, distribution, data on phenology, ecology, uses, Red List IUCN status, notes on taxonomy and biology and studied revised collections. Colour and characters of peduncles and seeds in the processing of their development were observed, described and illustrated by photos in details.